THE IMPACT OF WORK-LIFE BALANCE ON TURNOVER INTENTIONS: EXPLORING THE MEDIATING ROLE OF JOB SATISFACTION - Handayani, Reni; Faslah, Roni; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The aim of this study is to examine the impact of Work-Life Balance on Turnover Intention with a particular focus on Job Satisfaction as an intermediary variable among the workforce at PT X. The research employs a quantitative methodology. The study population included 155 employees, out of which a subset of 112 participants was selected for analysis. The methodological framework utilized in this study is causal modeling, also known as path analysis, which is used to investigate the interactions and influences among variables. Stratified random sampling was utilized to select study participants. Data collection was conducted using surveys featuring a Likert scale to measure responses. Analysis was conducted using SmartPLS 3.0, which includes assessments of both the Outer Model and Inner Model. The results of this study reveal that Work-Life Balance significantly and positively influences Turnover Intention. Similarly, Job Satisfaction has a positive and significant effect on Turnover Intention. Moreover, both Work-Life Balance and Job Satisfaction significantly and positively influence Turnover Intention, with Job Satisfaction serving as a key mediating factor in the linkage between Work-Life Balance and Turnover Intention.